Chiral symmetry, massive gluons and confinement - Natale, A. A. [UNESP] (2013)
It is quite difficult to obtain non-trivial chiral symmetry breaking solutions for the quark gap equation in the presence of dynamically generated gluon masses. An effective confining propagator has recently been proposed by Cornwall in order to solve this problem. We study phenomenological consequences of this approach, showing its compatibility with the experimental data. We argue that this confining propagator should be restricted to a small region of momenta, leading to effective four-fermion interactions at low energy. © 2013 American Institute of Physics.